OC-069 Rotational thromboelastometry in cirrhosis: hypercoagulable and hyperfibrinolytic. (28th May 2012) - Jairath, V; Hall, D; Harrison, P; Stanworth, S; Walsh, T; Hayes, P; Collier, J; Murphy, M; Barnes, E
Abstract : Introduction: Cirrhotics have complex acquired derangements of haemostasis. Routine coagulation tests suggest a hypocoagulable profile, resulting in frequent administration of blood components for prophylaxis and treatment of bleeding. Rotational thromboelastography (ROTEM ® ), unlike standard coagulation tests, provides a real-time measurement of clot formation, strength and stability in whole blood and may more accurately reflect in vivo coagulation. We aimed to (1) identify the key derangements in the haemostatic pathways in patients with cirrhosis; (2) determine the prevalence of overt hyperfibrinolysis and whether this could be improved with anti-fibrinolytics. Methods: We used ROTEM ® to investigate: (1) Clotting time (CT) and maximum clot firmness (MCF) in stable, non-bleeding cirrhotics compared to healthy volunteers; (2) The presence of overt hyperfibrinolysis and whether this could be reversed by spiking blood samples ex vivo with the antifibrinolytic aprotinin (APTEM test). Overt hyperfibrinolysis was defined by a maximum lysis (ML) of >15% and by comparing the clot lysis index at 60 min between EXTEM and APTEM parameters. Results: 106 adult cirrhotics and 28 healthy volunteers were enrolled after informed consent. Median EXTEM CT was shorter in cirrhotics than controls (51s vs 58s, p<0.01) and the clotting time shortened as Child-Pugh score increased in severity (52s Child A, 49s, Child B, 47s Child C). In cirrhotics there was strong correlation between EXTEM MCF with both platelet count (r=0.801, p<0.0001) and fibrinogen levels (r=0.653, p<0.0001), as well as fibrinogen and FIBTEM MCF (r=0.641, p<0.0001). 25% (26/106) of cirrhotics had evidence of overt hyperfibrinolysis. After spiking samples from cirrhotics with aprotinin, hyperfibrinolysis was completely reversed (ML<15%) in 50% (13/26) cases and partially reversed in 50% (13/26) cases. There was a significant reduction in the median ML between EXTEM and APTEM clot profiles (13 vs 11, p<0.001). D-dimer levels increased with increasing disease severity (Child A-894, Child B-1835, Child C-5281). Conclusion: Cirrhotics have a hypercoagulable clotting time, despite prolonged PT, APTT and thrombocytopenia supporting the concept of re-balanced haemostasis. Use of ROTEM ® may avoid unnecessary and potentially harmful transfusion of pro-coagulant blood components in cirrhotics. The high prevalence of overt hyperfibrinolysis in cirrhosis requires further elucidation and clinical studies to investigate the potential role of anti-fibrinolytics in the prophylaxis of variceal bleeding. Competing interests: None declared.